Comparison of the Physical Attributes of Plant-Based Ground Beef Alternatives to Ground Beef - K. M. Harr; S. G. Davis; S. B. Bigger; D. U. Thomson; M. D. Chao; J. L. Vipham; M. D. Apley; S. M. Ensley; M. D. Haub; M. D. Miesner; A. J. Tarpoff; K C Olson; et al. (Kansas Agricultural Experiment Station Research Reports, 2021)
Objective:The objective of this study was to evaluate the physical attributes of three different plant-based, ground beef alternatives in comparison to ground beef of three different fat percentages. Study Description:Ground beef of three different fat percentages, a retail pea protein-based ground beef alternative, and a traditional soy-based ground beef alternative were obtained from retail stores (n=15 lots/treatment). Samples from 15 lots of a foodservice soy protein-based ground beef alternative were obtained from a foodservice chain. All samples were fabricated into 0.25 lb patties assigned to one of four assays: color analysis, texture profile analysis, shear force, and pressed juice percentage. Results:When evaluating raw color, traditional ground beef alternative had the highest (P<0.05) a* value and were redder when compared to all other treatments, with retail ground beef alternative having the lowest (P<0.05) a* value. Traditional and retail ground beef alternative had the highest (P<0.05) a* value, while foodservice ground beef alternative, and 30% and 10% fat ground beef had the lowest (P<0.05) a* value for cooked surface color. For texture attributes, retail and foodservice ground beef alternatives had lower (P<0.05) values for cohesiveness, gumminess, hardness, and chewiness, as well as higher (P<0.05) values for springiness, than all other treatments evaluated. For shear force, the three ground beef alternatives were more tender (P<0.05) than all three ground beef treatments, with foodservice and retail ground beef alternatives being more tender (P<0.05) than all treatments. The three ground beef treatments had greater (P<0.05) pressed juice percentage values than all ground beef alternatives, indicating the ground beef was juicier than any of the ground beef alternatives evaluated. The Bottom Line:While the ground beef alternative products attempt to mimic ground beef, they provide very different color, texture, tenderness, and cooking characteristics than traditional ground beef.
Keywords: alternative proteins; ground beef; texture